The Regional Dimension of International Joint Ventures in Emerging Markets: A Comparison of Managerial Perception of Vietnam and Cote D’lvoire - Frank L. Bartels ,; Nick J. Freeman, (Asian Academy of Management Journal, 1998)
The Regional Dimension of International Joint Ventures in Emerging Markets: A Comparison of Managerial Perception of Vietnam and Cote D’lvoire(PDF not available)